71.6k views
4 votes
Simplify a and b:
a) 6x - 5y = 10x + 7
b) -4 +(-3) -(-9)
Plz hurry ⁉️‍♀️

User Ranel
by
6.1k points

1 Answer

3 votes

a) 6x - 5y = 10x + 7 SOLVING FOR X:

6x-5y=10x+7

−5y=10x+7−6x

−5y=4x+7

−5y−7=4x next divide both sides by four and switch sides


(-5y-7)/(4) =x


x=(-5y-7)/(4)

a) 6x - 5y = 10x + 7 SOLVING FOR Y:

6x-5y=10x+7

−5y=10x+7−6x then simplify

−5y=4x+7, now divide both sides by negative five


y=(4x+7)/(5)

b) -4 +(-3) -(-9)

-4+(-3)-(-9) Remove parentheses and simplify.

−4−3+9=−7+9=2

Hope this helps, now you know the answer and how to do it. HAVE A BLESSED AND WONDERFUL DAY! :-)

- Cutiepatutie ☺❀❤

User Deathfry
by
5.8k points